2006
DOI: 10.1177/1090198107311278
|View full text |Cite
|
Sign up to set email alerts
|

Ecodevelopmental × Intrapersonal Risk

Abstract: Hispanic adolescents are a rapidly growing population and are highly vulnerable to substance abuse and HIV infection. Many interventions implemented thus far have been "one size fits all" models that deliver the same dosage and sequence of modules to all participants. To more effectively prevent substance use and HIV in Hispanic adolescents, different risk profiles must be considered. This study's purpose is to use intrapersonal and ecodevelopmental risk processes to identify Hispanic adolescent subgroups and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 43 publications
2
30
0
Order By: Relevance
“…They expressed how difficult it is to reject the peer pressure “pushing” them to consume drugs. These findings confirm previous research indicating that many Latino youth residing in inner-city urban areas are exposed to intense peer pressure associated with drug use and abuse (Prado et al, 2009). …”
Section: Discussionsupporting
confidence: 91%
“…They expressed how difficult it is to reject the peer pressure “pushing” them to consume drugs. These findings confirm previous research indicating that many Latino youth residing in inner-city urban areas are exposed to intense peer pressure associated with drug use and abuse (Prado et al, 2009). …”
Section: Discussionsupporting
confidence: 91%
“…In summary, findings from five studies supported that adolescents' intentions to have sex and condom use are predictors of protected intercourse (Buhi & Goodson, 2007;Koniak-Griffin et al, 2003;Koniak-Griffin & Stein, 2006;Prado et al, 2009;Villarruel et al, 2004). Findings from four studies indicated positive relationships between adolescents' perceptions of normative beliefs or subjective norms about condom use and engagement in intercourse and adolescents' intentions to use condoms (Koniak-Griffin et al, 2003;Koniak-Griffin & Stein, 2006;Villarruel et al, 2004) and adolescents' sexual activity (Buhi & Goodson, 2007).…”
Section: Relationship Between Adolescents' Attitudes Subjective Normmentioning
confidence: 73%
“…The authors also found positive association between adolescents' perceptions of parents' approval of condom use and their intentions to use condoms; and a positive association between adolescent condom use self-efficacy and intentions to use condoms. Prado et al (2009) found that condom use social norms were not significantly associated with attitudes about sex, social norms regarding sex, or sexual intentions. Also condom use intentions were not correlated with sexual intentions.…”
Section: Relationship Between Adolescents' Attitudes Subjective Normmentioning
confidence: 92%
See 1 more Smart Citation
“…The extent and quality of their interactions with both their cultures of origin and the U.S. culture, and the cultural identities they adopt personally, may influence their decisions about engaging in health-promoting and health-compromising behaviors (Guzman, Santiago-Rivera, & Hasse, 2005; Marcell, 1994; Umaña-Taylor & Fine, 2001). Indeed, research reveals significant variation in adolescent substance use across national subgroups such as Mexican Americans, Puerto Ricans, Cuban Americans, and Salvadoran Americans (Delva et al, 2005; Prado et al, 2009; Vaeth, Caetano, Ramisetty-Mikler, & Rodriguez, 2009) and among first-, second-, and third-generation Hispanic Americans (Eitle, Wahl, & Aranda, 2009), as well as associations between substance use and acculturation (Bethel & Schenker, 2005; Castro, Stein, & Bentler, 2009; De La Rosa, 2002; Eitle et al, 2009; Marsiglia, Kulis, Hussaini, Nieri, & Becerra, 2010; Unger et al, 2000; Zamboanga, Schwartz, Jarvis, & Van Tyne, 2009). …”
mentioning
confidence: 99%